Treatment of Used lubricant Oil by Solvent Extraction - Altaee, Tariq; Rashid, Sarmad A.; Abdul Jabbar, Marwa F. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
This study investigates the treatment of used lubricating oils from AL-Mussaib Gas Power Station Company-Iraq, which was treated with different extractive solvents (heptane and 2-propanol). The performance activity of these solvents in the extraction process was examined and evaluated experimentally. Operating parameters were solvent to oil ratios of (1:2, 1:4, 1:6, and 1:8), mixing time (20, 35, 50, and 65 min), temperatures (30, 40, 50, and 60 ºC), and mixing speed (500 rpm). These parameters were studied and analyzed. The quality is determined by the measuring and assessment of important characteristics specially viscosity, viscosity index, specific gravity, pour point, flash point, and ash content. The results confirm that the solvent 2-Propanol gave great proficiency with the most elevated percent of sludge removal compared with heptane. The greatest percentage of waste removal is enhanced when the solvent/oil ratio increases with optimal economic aspects. The significant characteristics of the reused lubricating oil were estimated. The outcome of the results indicates that the adjustment of the characteristics of reused oil has great effectiveness and the best working conditions for 2-Propanol (35 min, 1:6 S/O ratio, 40 ºC), and heptane (50 min, 1:6 S/O ratio, 50 ºC).